Auctions and corruption - Yvan Lengwiler; Elmar Wolfstetter (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
In many auctions, the auctioneer is an agent of the seller. This delegation invites corruption. In this paper we propose a model of corruption, examine how corruption affects the auction game, how the anticipation of corruption affects bidding, and how it altogether changes the revenue ranking of typical auctions. In addition we characterize incentive schemes that may prevent corruption, and compare them to the fee schedules employed by major auction houses.
urn:nbn:de:kobv:11-10047498
Keywords: D44; 330; auctions; procurement; corruption; collusion; coalitions